Quantitative analysis of peripapillary RNFL capillary density and thickness in patients with mild nonproliferative diabetic retinopathy - Cao, Zelie; Tian, Tao; Liu, Ru; Peng, Jinli; Kuang, Guoping (Frontiers in Endocrinology, 2025)
PurposeOptical coherence tomography angiography was used to compare the changes of capillary density and thickness of the peripapillary retinal nerve fiber layer in patients with diabetes mellitus (DM) without diabetic retinopathy (DR) and patients with mild nonproliferative diabetic retinopathy (NPDR).MethodsIn this prospective cross-sectional study, 62, 85, and 75 eyes of normal control group (NC), DM group, and NPDR group were included, respectively. All subjects received an optic-disc-centered 6 × 6-mm fundus scan. The annular region outside the optic disc boundary was divided into eight sectors: nasal superior, nasal inferior, inferior nasal (IN), inferior temporal (IT), temporal superior, temporal inferior, superior nasal, and superior temporal (ST). The average retinal nerve fiber layer thickness, average capillary density, and changes in thickness and capillary density of each sector in the annular region were calculated.ResultsCompared with the NC group, the average capillary density of pRNFL in patients with DM and NPDR groups decreased significantly (p < 0.001), and there were significant differences in capillary density in all sectors except the IN sector in the DM group. There was no significant difference in the average thickness of pRNFL between the groups. Only the thickness of ST and IT in DM group and NPDR group, respectively, were significantly lower than that in the control group. In addition, the ROC curve of pRNFL average capillary density has high sensitivity and specificity in distinguishing DR from healthy eyes (AUC = 0.852).ConclusionThe pRNFL average capillary density in diabetic patients without DR and patients with mild NPDR, respectively, were significantly lower than that in healthy controls, especially in the NPDR group.